Vertical sleeve gastrectomy increases duodenal Lactobacillus spp. richness associated with the activation of intestinal HIF2α signaling and metabolic benefits - Yikai Shao; Simon S. Evers; Jae Hoon Shin; Sadeesh K. Ramakrishnan; Nadejda Bozadjieva-Kramer; Qiyuan Yao; Yatrik M. Shah; Darleen A. Sandoval; Randy J. Seeley (Elsevier, 2022)
Objective: Vertical Sleeve Gastrectomy (VSG) is one of the most efficacious treatments for obesity and its comorbidities. Although a range of evidence suggests that alterations of the microbiota in the distal gut following VSG are pivotal to these metabolic improvements, the effect of surgery to alter the microbiota of the proximal intestine and its effect on host physiology remain largely unknown. As the main bacteria in the upper small intestine, Lactobacillus subspecies have been appreciated as important regulators of gut function. These bacteria also regulate intestinal Hypoxia- Inducible Factor 2α (HIF2α) signaling that plays an integral role in gut physiology and iron absorption. In the present study, we sought to determine the impact of VSG on Lactobacillus spp. in the small intestine and potential downstream impacts of Lactobacillus spp. on HIF2α, specifically in the duodenum. Methods: To determine the effects of VSG on the microbiota and HIF2α signaling in the duodenum, VSG surgeries were performed on diet-induced obese mice. To further probe the relationship between Lactobacillus spp. and HIF2α signaling in the duodenum, we applied a customized high-fat but iron-deficient diet on mice to increase duodenal HIF2α signaling and determined alterations of gut bacteria. To explore the causal role of Lactobacillus spp. in duodenal HIF2α signaling activation, we chronically administered probiotics containing Lactobacillus spp. to high-fat-fed obese mice. Lastly, we studied the effect of lactate, the major metabolite of Lactobacilli, on HIF2α in ex vivo duodenal organoids. Results: There were pronounced increases in the abundance of Lactobacillus spp. in samples isolated from duodenal epithelium in VSG-operated mice as compared to sham-operated mice. This was accompanied by an increase in the expression of genes that are targets of HIF2α in the duodenum of VSG-treated mice. Activating HIF2α signaling with a high-fat but iron-deficient diet resulted in weight loss, improvements in glucose regulation, and increased Lactobacillus spp. richness in the duodenum as compared to mice on an iron-replete diet. Chronic administration of probiotics containing Lactobacillus spp. not only increased HIF2α signaling in the duodenum such as occurs after VSG but also resulted in reduced weight gain and improved glucose tolerance in high-fat-fed mice. Furthermore, lactate was able to activate HIF2α in ex vivo duodenal organoids. Conclusions: These results support a model whereby VSG increases duodenal Lactobacillus richness and potentially stimulates intestinal HIF2α signaling via increased lactate production.